Charade Game: Does it Impact Students’ Writing Ability? - Abdullah Al Azhar; Entika Fani Prastikawati; Siti Musarokah (Universitas PGRI Semarang, 2023)
Modern English instruction must show a developing strategy to motivate and inspire pupils. Introducing games into the teaching and learning process is an option for reducing student boredom. The game of Charade is one alternate teaching strategy that can be used to teach English writing and improve students' writing skills. This study utilized the Charade game as a teaching method for writing. Utilizing a pre-test and post-test, a quasi-experimental research method was implemented. 30 students were assigned to each of the control and experimental groups, for a total of 60. After a series of interventions, students' writing skills were assessed. The outcome of quantitative data analysis was performed using SPSS 25. Compared to the control group, the experimental group demonstrates a considerable change and improvement in writing skills. The significant improvement of the experimental group demonstrates the efficacy of the Charade game as a method for teaching writing.